The Influence of Work Discipline and Work Conflict on Perfoemance throuch Work Morale as an Intervening Variable at Satpol PP East Kutai regency - Majid, Abdul; Latif, Imam Nazarudin; Permana, Meiki (Economic Reviews Journal, 2025)
This study aims to analyze the determinants of Employee Performance at the Civil Service Police Unit (Satpol PP) of East Kutai Regency. This study is motivated by the challenges of fieldwork that require high discipline and mental resilience in facing potential conflicts, which impact organizational performance. The variables tested include Work Discipline (X1) and Work Conflict (X2) as independent variables, and Work Morale (Z) as an intervening variable. The research method uses an associative quantitative approach. The sample consisted of 105 respondents from a total population of 142 employees, determined using the Slovin formula with the Proportionate Stratified Random Sampling technique. Data analysis was carried out using SEM-PLS with the help of WarpPLS 8.0 software. The test results show that Work Discipline has a positive and significant influence on both Work Morale and Employee Performance, and is the most dominant variable. Interestingly, Work Conflict was found to have a positive and significant influence on Employee Performance, confirming the existence of productive functional conflict, although Work Conflict did not have a significant influence on Work Morale. Work Morale was shown to act as a partial mediator, especially in mediating the influence of Work Discipline on Performance. These findings suggest that organizations should focus on enforcing discipline and maintaining morale to maximize employee performance.